Impact of COVID-19 Pandemic on Treatment Management and Clinical Outcome of Aneurysmal Subarachnoid Hemorrhage – A Single-Center Experience - Kashefiolasl, Sepide; Qasem, Lina Elisabeth; Brawanski, Nina; Funke, Moritz; Keil, Fee; Hattingen, Elke; Foerch, Christian; Seifert, Volker; Prinz, Vincent Matthias; Czabanka, Marcus; Konczalla, Juergen (Frontiers in Neurology, 2022)
Background Previous studies reported decreased volumes of acute stroke admissions during the COVID-19 pandemic. We aimed to examine whether aneurysmal subarachnoid hemorrhage (aSAH) volumes demonstrated similar declines in our department. Furthermore, the impact of pandemic on disease progression should be analyzed. Methods We conducted a retrospective study in neurosurgical department of university hospital Frankfurt including patients with the diagnosis of aneurysmal SAH during the first year of COVID-pandemic. One year cumulative volume for aSAH hospitalization procedures were compared to the one-year period before (03/2020 – 02/2021 versus 03/2019 – 02/2020) and the last 5 pre-COVID-pandemic years (2015-2020). All relevant patient characteristics concerning family history, disease history, clinical condition at admission, active/past COVID-infection, treatment management, complications and outcome were analyzed. Results Compared to the 84 hospital admissions during the pre-pandemic year, number of aSAH hospitalizations (n=56) was declined during the pandemic, without reaching a significance. No significant difference in analyzed patient characteristics including clinical condition at onset, treatment, complications and outcome, between 56 aSAH patients admitted during COVID pandemic and treated patients in the last 5 years in pre-COVID period were found. In our multivariable analysis, we detected young age (p<0.05; OR 4.2) and no existence of early hydrocephalus (p<0.05; OR 0.13) as important factors for a favorable outcome (mRS≤0-2) after aSAH during the COVID-pandemic. A past COVID-infection was detected in young patients suffering from aSAH (Age<50years, p<0.05; OR 10.5) with increased rate of cerebral vasospasm after aSAH onset (p<0.05; OR 26). Nevertheless, past COVID-infection did not reach a significance as a high risk factor for unfavorable outcome. Conclusion There was a relative decrease in the number of aSAH patients during the COVID-19 pandemic. Despite of extremely different conditions of hospitalization, there was no impairing significant effect on treatment and outcome of admitted aSAH patients. A past COVID-infection seemed not to be a relevant limiting factor concerning favorable outcome.